The Use of Teaching Algerian Dialects in Algeria to Undermine Standard Arabic during the French Colonial Period - braham, samir (El Omda in Linguistics and Discourse Analysis, 2022)
After the occupation of Algeria, the colonial authorities established several institutes dedicated to the study and teaching of Arabic and Amazigh dialects. Among the most important of these institutions was the Higher School of Arts in Algiers, later transformed into the Faculty of Arts, as well as the École Normale in Bouzareah, Algiers. These educational structures received extensive support from the colonial administration, particularly from the Ministry of Defense, which directly supervised researchers working in these fields. Some of these researchers were even officers in the colonial army, such as Hanoteau. However, these studies were not driven by purely scientific objectives; rather, they aimed to reinforce and consolidate colonial control over Algeria.